2015
DOI: 10.1111/1556-4029.12953
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Intoxication with Acetyl Fentanyl

Abstract: Among the new psychoactive substances encountered in forensic investigations is the opioid, acetyl fentanyl. The death of a 28-year-old man from recreational use of this compound is reported. The decedent was found in the bathroom of his residence with a tourniquet secured around his arm and a syringe nearby. Postmortem examination findings included marked pulmonary and cerebral edema and needle track marks. Toxicological analysis revealed acetyl fentanyl in subclavian blood, liver, vitreous fluid, and urine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 19 publications
4
45
1
1
Order By: Relevance
“…As described in our previous report, the concentrations of mepirapim in blood specimens were much higher than those of various other synthetic cannabinoids (0.1-199 ng/mL) in previous reports of poisoning deaths [2,[18][19][20]. On the other hand, the concentrations of acetyl fentanyl in the femoral vein and heart whole blood were at levels relatively similar to those of previous reports; the acetyl fentanyl blood levels in fatal cases were 6-600 ng/mL [10], 250-260 ng/mL [11], 153 ng/mL [12], 270 ng/mL [13], 192-285 ng/mL [14] and 235 ng/mL [15]. The urinary level of unchanged mepirapim in the deceased individual was also as high as 309 ng/mL, although the concentration was slightly lower than that previously found (527 ng/mL) [4].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As described in our previous report, the concentrations of mepirapim in blood specimens were much higher than those of various other synthetic cannabinoids (0.1-199 ng/mL) in previous reports of poisoning deaths [2,[18][19][20]. On the other hand, the concentrations of acetyl fentanyl in the femoral vein and heart whole blood were at levels relatively similar to those of previous reports; the acetyl fentanyl blood levels in fatal cases were 6-600 ng/mL [10], 250-260 ng/mL [11], 153 ng/mL [12], 270 ng/mL [13], 192-285 ng/mL [14] and 235 ng/mL [15]. The urinary level of unchanged mepirapim in the deceased individual was also as high as 309 ng/mL, although the concentration was slightly lower than that previously found (527 ng/mL) [4].…”
Section: Discussionsupporting
confidence: 88%
“…Further, our detailed analyses revealed that the highest levels of acetyl fentanyl were distributed to the myocardium, kidney and spleen rather than to the liver and brain. These postmortem distribution results may provide new insight into the excretion, pharmacokinetics and metabolism of acetyl fentanyl in a case of fatal poisoning after intravenous exposure, although previous reports dealing with the distribution of acetyl fentanyl did not include the myocardium and kidney [10,11,15].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The proportion of illicit drug overdose deaths involving fentanyls has grown in Canada during the last few years to exceed 50% in some parts of the country 14, 15, 16. Since 2012, 12 deaths in Russia17 and more than 50 deaths in the USA have been associated with acetylfentanyl 18, 19, 20, 21, 22. Other fentanyl analogues, such as butyrfentanyl, 3‐methylfentanyl, and furanylfentanyl, have also been linked to serious adverse events 23, 24, 25.…”
Section: Introductionmentioning
confidence: 99%